Superior women medieval female authority in Poitiers' Abbey of Sainte-Croix - Edwards, Jennifer C. ca. 20./21. Jh (Oxford University Press, 2019)
This work tells the story of how the abbesses of the monastery of Sainte-Croix in Poitiers, France gained the respect and support of powerful male officials, such as the king and the pope, throughout the Middle Ages, primarily by drawing upon the strategies for winning support of Saint Radegund, a sixth century queen and founder of the monastery
Includes bibliographical references and index
Keywords: Abbaye Sainte-Croix de Poitiers / History; Abbaye Sainte-Croix -- Poitiers; Geschichte; Abbesses, Christian / France / Poitiers / History; Power (Social sciences) / France / History / To 1500; Mittelalter; Frau; Äbtissin; Macht; France / History / Medieval period, 987-1515